The zinc transporter, ZIP12, regulates the pulmonary vascular response to chronic hypoxia - Zhao,L; Oliver,E; Maratou,K; Atanur,SS; Dubois,OD; Cotroneo,E; Chen,CN; Wang,L; Arce,C; Chabosseau,PL; Ponsa-Cobas,J; Frid,MG; et al. (Nature, 2015)
The typical response of the adult mammalian pulmonary circulation to a low oxygen environment is vasoconstriction and structural remodelling of pulmonary arterioles, leading to chronic elevation of pulmonary artery pressure (pulmonary hypertension) and right ventricular hypertrophy. Some mammals, however, exhibit genetic resistance to hypoxia-induced pulmonary hypertension1, 2, 3. We used a congenic breeding program and comparative genomics to exploit this variation in the rat and identified the gene Slc39a12 as a major regulator of hypoxia-induced pulmonary vascular remodelling. Slc39a12 encodes the zinc transporter ZIP12. Here we report that ZIP12 expression is increased in many cell types, including endothelial, smooth muscle and interstitial cells, in the remodelled pulmonary arterioles of rats, cows and humans susceptible to hypoxia-induced pulmonary hypertension. We show that ZIP12 expression in pulmonary vascular smooth muscle cells is hypoxia dependent and that targeted inhibition of ZIP12 inhibits the rise in intracellular labile zinc in hypoxia-exposed pulmonary vascular smooth muscle cells and their proliferation in culture. We demonstrate that genetic disruption of ZIP12 expression attenuates the development of pulmonary hypertension in rats housed in a hypoxic atmosphere. This new and unexpected insight into the fundamental role of a zinc transporter in mammalian pulmonary vascular homeostasis suggests a new drug target for the pharmacological management of pulmonary hypertension.